Estrategias didácticas para el mejoramiento de la enseñanza-aprendizaje en los estudiantes con dificultades de motricidad gruesa presentados posterior a la pandemia, en el segundo grado de educación básica paralelo "b" de la "Unidad Educativa Misahualli" cantón Tena, provincia Napo en el periodo académico 2022- 2023 - Lasluisa Lasluisa, Lidia Maricela (2023)
This research is focused on the descriptive study of the didactic strategies for the improvement of teaching-learning in students with gross motor difficulties presented after the pandemic in the second grade of Basic Education parallel “B” of the “Misahualli Educational Unit” Tena Canton, Napo Province in the academic period 2022-2023, since the objective was to determine the importance and use of the same, to improve the development of gross motor skills in the teaching-learning process. This work presented the qualitative approach and for data collection an observation guide was applied to the population of 18 students and a teacher with whom we worked. In this way, it was possible to determine some of the difficulties presented by the students in the development of their body movement. In this sense, a proposal for a guide of didactic strategies was elaborated through games in the development of gross motor skills to improve children ́s learning. Therefore, through the application of playful activities it was possible to improve the balance, laterality, dynamic coordination of the children especially this type of activities allows to keep them motivated and in a constant body movement so that their learning is meaningful and to maintain a healthy and healthy life. In addition to this, it allowed the teacher to strengthen the teaching-learning process.